A scanning method for the identification of pottery forming techniques at the mesoscopic scale: A pilot study in the manufacture of Early Bronze Age III holemouth jars and platters from Tell es-Safi/Gath. (April 2018) - Ross, Jon; Fowler, Kent D.; Shai, Itzick; Greenfield, Haskel J.; Maeir, Aren M.
Abstract: In this paper, we propose an alternative analytical method for identifying vessel shaping techniques at the mesoscopic scale to complement current micro and macro methods in ceramic analysis. We demonstrate how this simple and low cost method permits clear and rapid identification of the signatures indicative of different pottery shaping techniques. The datasets that are generated using this method provide a new perspective on vessel structure for characterising neglected stages of the chaîne opératoire, with the analytical potential to shed further light on economic life, learning frameworks, and group identities. Material from the Early Bronze Age III of Tell eṣ-Ṣâfi/Gath, Israel are used to demonstrate the utility of the method on a site assemblage. We identify different combinations of coiling techniques used to make different vessel types and propose that potters are specialising in the production of specific parts of the repertoire.